Pengaruh Label QR Code Produk Original dan Harga terhadap Keputusan Pembelian pada Produk MS Glow (Studi Kasus pada Konsumen di Pati) - Yusdianti, Wiwin; Hartono, Budi (Jurnal Nasional Manajemen Pemasaran dan SDM, 2022)
In this modern era, developments in various industries are growing very fast, giving rise to intense competition. One of them is the cosmetics and skincare industry. This study aims to analyze the effect of the original product qr code label and price on purchasing decisions on Ms Glow products. The study used a quantitative approach by distributing online questionnaires to 50 consumer respondents from Ms Glow in Pati. The data collected were analyzed using multiple linear regression model using SPSS version 26 program. The results showed that the original product qr code label variable and price had a simultaneous effect on the purchasing decision variable. The results of the study have implications for Ms Glow to pay attention to prices because prices can influence purchasing decisions for Ms Glow products. And for further researchers can develop research by adding other variables that can influence consumer purchasing decisions so that research becomes more perfect.